Executive Committee Minutes 2020-11-12 - Academic Senate:::::::::
Agenda – Approved. Minutes of 10/29/2020 – Approved. Chair Report. President Report. Provost Report. Vice President for Student Affairs Report. Statewide Senator Report. Vice President of Administration and Finance Report. FSAC Report. SAC Report. CFA Report. SETE release deadline. Faculty Retreat Planning. Senate Agenda Approved. Good of the Order.